AKTIVITAS PENGHAMBATAN ISOLAT BAKTERI ASAM LAKTAT IKAN NILA DAN TONGKOL TERHADAP BAKTERI MERUGIKAN PRODUK PERIKANAN - Rinto .; Ade Dwi Sasanti; Kusumawati Fitria (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Lactic acid bacteria were known has a potential for biopreservative and maintaining the safety of food products. The purpose of this research was to obtain lactic acid bacteria that capable to inhibit harmful bacteria in fisheries products. The stages of the methods were isolation of lactic acid bacteria from the digestive tract tilapia and frigate tuna with MRS agar + CaCO3, antibacterial test against Bacillus subtilis, Morganella morganii, and Escherichia coli using agar well diffusion method and test the alleged strengthening  lactic acid bacteria. The results showed that there were two isolates of lactic acid bacteria that have the greatest inhibitory for harmful bacteria tested.Key words: antibacterial, biopreservative, inhibitor harmful bacteria, lactic acid  bacteria